The SASA dictionary and its sources: Statistical method of analysis and its application in the presentation of lexical corpus material - Jošić Neđo G.; Tomić Bojana N. (Južnoslovenski Filolog)
The sources of the Dictionary of Serbo-Croatian Literary and Vernacular Language, vol. 1-21 (the SASA Dictionary or Dictionary of the Serbian Academy) are analyzed applying the method of statistical analysis. Its main aim was to provide a clear idea of the frequency of relevant and particularly relevant sources in the text of the dictionary as a whole (while also pointing to the problems and hindrances that occur in the digital search of sources). This type of analysis was conducted using the volumes 2, 10 and 17 (released in 1962, 1978, and 2006, respectively). The analysis and total ratio of frequency in the volumes under examination demonstrates that the sources can be divided into: a. The basic circle (top 10 dictionary sources); b. Broader circle (top 100 sources); c. The broadest circle (top 500 sources). The analysis also yielded the fact that basic sources comprise more important dictionaries as well as collections of vernacular words, so that the circle of sources spreads further including some other more relevant collections of words, prominent authors, significant periodicals, and so on. The analysis as projection basically identified the sources upon which the SASA Dictionary is actually based. Beyond this varied and broad circle lie sources that more rarely, or hardly ever occur, as a testimony to the existence or usage of certain lexical items in the corpus material of the Dictionary of the Serbian Academy. The said indicators point the way to the further process of digitization of the SASA Dictionary and its corpus material.